A comparison of cytological quality between fine‐needle aspiration and non‐aspiration techniques for obtaining ultrasound‐guided samples from canine and feline lymph nodes. (10th February 2021) - Whitlock, James; Taeymans, Olivier; Monti, Paola
Abstract: Background : In small animal medicine, ultrasound‐guided fine‐needle lymph node sampling plays a pivotal role in the diagnostic investigation of a range of pathologies including the staging of neoplastic disease. Traditionally fine needle aspiration cytology (FNAC) has been employed to produce samples, but fine needle non‐aspiration cytology (FNNAC) has been suggested to generate superior sample quality and diagnosticity. Methods : In a randomised control trial, 104 canine and feline lymph nodes were each sampled by both techniques. The cytological samples were then submitted to pathologists who were blinded to the technique used to generate each sample. They determined if the sample was diagnostic or non‐diagnostic and graded the sample in terms of the degree of cellularity, cellular preservation and haemodilution. Results : It was found that lymph node samples obtained using the FNAC technique were more likely to be diagnostic (p = 0.043) than samples obtained using the FNNAC technique. In addition, FNAC samples had significantly higher cellularity than FNNAC counterparts (P = 0.043). No significant difference in cell preservation or haemodilution was found between samples from the FNAC and FNNAC groups. Conclusion : In this study, FNAC was superior to non‐aspiration cytology for the sampling of canine and feline lymph nodes as it generated a higher number of diagnostic samples with greater cellularity.